Memaknai Kesatuan Orang-orang Percaya menurut Yohanes 17:20-23 - Nicholas Raja Hatigoran Nababan; Jefit Sumampouw (KHARISMATA: Jurnal Teologi Pantekosta, 2023)
This article examines John 17 about the theological meaning of unity. In the midst of the many denominations and teachings of Christianity, this passage has significance for the diversity of the church today. Interpreting this biblical passage will answer the many meanings of this topic. The meaning of being one is investigated using available sources from scholars specializing in the Gospel of John. The result, using qualitative data in the form of literature, which shows that the meaning of the passage is not about the unity of the entire organization of believers, but the unity that occurs in Christ. Under these conditions, every church will have one direction to glorify God's name in His eternal plan.Penelitian ini mengkaji Yohanes 17 tentang makna kesatuan secara teologis. Di tengah banyaknya denominasi dan ajaran kekristenan maka perikop ini memiliki signifiknasi bagi keragaman gereja saat ini. Memaknai dengan biblikal perikop ini akan menjawab banyaknya pemaknaan dari topik ini. Makna dalam menjadi satu diinvestigasi menggunakan sumber-sumber yang ada dari sarjana yang khusus mendalami Injil Yohanes. Hasilnya, dengan menggunakan data kualitatif berupa literatur kepustakaan, di mana menunjukkan bahwa makna dari perikop bukan tentang kesatuan seluruh organisasi orang percaya, tetapi kesatuan yang terjadi dalam Kristus. Dengan kondisi itu maka setiap gereja akan memiliki arah yang satu untuk memuliakan nama Allah dalam rencana kekal-Nya.